A robust discriminative multi-atlas label fusion method for hippocampus segmentation from MR image. (September 2021) - Wang, Wenna; Zhang, Xiuwei; Ma, Yu; Cui, Hengfei; Xia, Rui; Zhang, Yanning
Highlights: The computational cost is reduced compared with classical "coarse-fine" registration stage by adopting the resampling algorithm in the coarse registration stage. A patch embedding segmentation approach based on conditional random field (CRF) model potentially improves the segmentation performance of the hippocampus. Furthermore, considering the label map rich in prior information is not fully used, the segmentation results are refined based on SPBM method. Compared with state-of-the-art methods, our proposed method can obtain more accurate hippocampus segmentation results. Abstract: Accurate and automatic segmentation of the hippocampus plays a vital role in the diagnosis and treatment of nervous system diseases. However, due to the anatomical variability of different subjects, the registered atlas images are not always perfectly aligned with the target image. This makes the segmentation of the hippocampus still face great challenges. In this paper, we propose a robust discriminative label fusion method under the multi-atlas framework. It is a patch embedding label fusion method based on conditional random field (CRF) model that integrates the metric learning and the graph cuts by an integrated formulation. Unlike most current label fusion methods with fixed (non-learning) distance metrics, a novel distance metric learning is presented to enhance discriminative observation and embed it into the unary potential function. In particular, Bayesian inference is utilized to extend a classic distance metric learning, in which large margin constraints are instead of pairwise constraints to obtain a more robust distance metric. And the pairwise homogeneity is fully considered in the spatial prior term based on classification labels and voxel intensity. The resulting integrated formulation is globally minimized by the efficient graph cuts algorithm. Further, sparse patch based method is utilized to polish the obtained segmentation results in label space. The proposed method is evaluated on IABA dataset and ADNI dataset for hippocampus segmentation. The Dice scores achieved by our method are 87.2 %, 87.8 %, 88.2 % and 88.9 % on left and right hippocampus on both two datasets, while the best Dice scores obtained by other methods are 86.0 %, 86.9 %, 86.8 % and 88.0 % on IABA dataset and ADNI dataset respectively. Experiments show that our approach achieves higher accuracy than state-of-the-art methods. We hope the proposed model can be transferred to combine with other promising distance measurement algorithms.